Combination Therapy in Melasma with Lentigo Solaris: Case Report - Lumbantoruan, Erty Witalaya; Nasution, Khairina; Nelva Karmila Jusuf (Talenta Publisher, 2020)
Background: Melasma and lentigo solaris are common, recurrent, and refractory acquired hyperpigmentation disorder. In spite of variety of therapeutic options available for this cosmetically disfiguring condition, the treatment of this condition remains a challenge. Azelaic acid (AA) is a depigmenting agent which acts by inhibition of DNA synthesis and mitochondrial enzymes, thereby inducing direct cytotoxic effects on melanocytes. Glycolic acid (GA) peel is one of the most versatile agents in the treatment of melasma and lentigo solaris. GA peels alone or in combination with topical hypopigmenting agents has shown encouraging results. However, there is paucity of controlled trial demonstrating the efficacy of GA peels in conjunction with topical AA. Case: A 42-years-old female, works as a street vendor, came with dark brown spots on both cheeks, nose, chin and forehead that spreads to whole face since one year ago. She had a history of using contraceptives. From the dermatological examination, there were multiple well-circumscribed, irregular hyperpigmented macules that asymmetrical, with size ranging from lenticular to plaque on the maxillary, left buccalis, mentalis and frontalis region. We also found a numular dark brown hyperpigmented macules on right zygoma. She was diagnosed with melasma and lentigo solaris. The Melasma Area Severity Index (MASI) score was 25.6, which classified as moderate melasma. She was treated with 20% azaleic acid cream twice a day, broadspectrum sunscreen with SPF 50 and GA 20% peeling. Result: After 6 weeks of treatment, there were significant improvement in both melasma and lentigo solaris.